Die Persistenz der Ordnung - Abdin, Eimen (2023)
Society is fundamentally political and contingent. And yet politics is a tough and energy-sapping struggle for hegemony, and the foundations of the social order appear unshakeable despite various attempts at change. Drawing on Ernesto Laclau's formulation of a theory of hegemony and discourse and its Heideggerian continuation by Oliver Marchart, Eimen Abdin shows the persistence underlying every order, which must be taken into account during political upheaval. In this study, starting from the ontology of the political implied by Laclau and revealed by Marchart, Abdin designs an ontology of power that follows on from Heidegger.